"RELATIONSHIP BETWEEN ECONOMIC INEQUALITY AND SOCIAL INEQUALITY" - Nutan Kumari (International Journal of Multidisciplinary Research and Studies, 2021)
In recent years, there has been a growing concern about the rising income inequalities, with particularly stark rises in inequality in the United States and also a substantial widening of the income gap in Europe. This has led to a growing number of voices expressing their disapproval of these trends. The significance of the expansion of economic disparities has not only attracted the attention of politicians and academics, but it is also widely discussed on the streets of the world today, with the ’Occupy Wall Street’ movement being the most famous example of such demonstrations. This movement and its frequently referenced motto, "We are the 99%," alludes explicitly to a rising disparity in the distribution of wealth (see, for example, the coverage of the movement by the New York Times in 2011, as well as the web blog entitled "We are the 99%," published in 2012). An OECD report that was released not too long ago focused on the recent rise in income disparity that has been seen throughout the member nations of the EU (2011). An intriguing picture emerges when one examines the evolution of income disparity over the course of the last three decades. Beginning in the 1980s, there appears to have been a general tendency toward increasing the economic disparity between different groups of people. In the 1980s, the Gini coefficient was calculated at 0.29, but by the late 2000s, it had significantly increased to 0.32. The rise in economic disparity in nations that were once considered to be "equal societies," such as Germany and the Nordic countries, is particularly startling. In general, there appears to be a tendency that is converging towards a generally larger degree of income disparity.